2016
DOI: 10.1002/cncr.30425
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of and adherence to tamoxifen and aromatase inhibitor therapy among elderly women with ductal carcinoma in situ

Abstract: BACKGROUND The National Surgical Adjuvant Breast and Bowel Project B35 and International Breast Cancer Intervention Studies II Ductal carcinoma In Situ (DCIS) trials showed similar treatment effects of anastrozole and tamoxifen in reducing cancer recurrence risk among DCIS patients, but the current body of literature lacks information on the five year adherence rates for these drugs from population-based studies. METHODS This study evaluated the initiation and 5-year adherence for women aged 66 to 85 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
2
23
3
1
Order By: Relevance
“…10 More recently, older women who underwent lumpectomy for in situ disease were also more likely to omit hormonal blockade when no adjuvant radiation was delivered. 17 They found that women were more likely to initiate hormonal blockade if they received RT, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…10 More recently, older women who underwent lumpectomy for in situ disease were also more likely to omit hormonal blockade when no adjuvant radiation was delivered. 17 They found that women were more likely to initiate hormonal blockade if they received RT, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Although this number may appear high, it is similar to the findings of a National Cancer Data Base analysis of older women in which the omission of RT was accompanied by a 46% rate of omission of hormonal blockade . More recently, older women who underwent lumpectomy for in situ disease were also more likely to omit hormonal blockade when no adjuvant radiation was delivered . They found that women were more likely to initiate hormonal blockade if they received RT, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tamoxifen by women with ER þ DCIS has proven value, both for prevention of new primaries, and for prevention of local recurrence, but its impact is mitigated by variable acceptance of tamoxifen therapy by women with DCIS and uncertainties about adherence following initial acceptance. Recent data from health systems and large databases show that the acceptance of tamoxifen therapy following local therapy for DCIS ranges from 22% to 45% (7,33,34). At our institution, a previous analysis that included 99 premenopausal women with DCIS found that tamoxifen initiation occurred in 58% (6).…”
Section: Discussionmentioning
confidence: 83%
“…These therapies are considered either before or after surgery based on the patients’ needs. Given that nearly 75% of BCa express estrogen and/or progesterone receptors, the majority of BCa patients receive either tamoxifen or aromatase inhibitors (AIs) (e.g., anastrozole, exemestane, or letrozole) on a long term basis (5–10 years) to decrease the risk of BCa recurrence …”
Section: Introductionmentioning
confidence: 99%